A MODIFICATION OF GAUSS' METHOD FOR PRELIMINARY DETERMINATION OF A CELESTIAL BODY'S ORBIT - Bazyey, A. A. (Одеські астрономічні публікації, 2016)
A modification of classical Gauss’ method for determination of Keplerian elements from the observed positions is considered in this paper. The modification involves the exhaustive enumeration of all possible orbital plane positions in order to improve the method’s reliability. It has been shown that such an approach requires a priori information on the pattern of the celestial body's motion, particularly, whether its motion is direct or retrograde.